Factors influencing digital skill competencies among persons with disabilities in Malaysia - Wok, Saodah; Hashim, Junaidah; Abdul Rahman, Rozailin; Haque, Ahasanul (2018)
Malaysia has about half a million persons with disabilities registered with the Department of Social Welfare. This study, therefore, tries to determine factors influencing digital skill competencies (technical competency, cognitive competency, and personal competency) among persons with disabilities. The factors explored are intensity of Internet usage, perception of the Internet, benefits of the Internet, and usage of the electronic devices. This study employs a quantitative research design using the survey method where a questionnaire is used as the research instrument. A total of 1200 persons with disabilities participated in the study. The impairment is either visual, hearing, speech, learning, physical or mental. Results show that the majority (84.1%) use the Internet. All factors correlate positively with the digital skill competencies. The best predictor is the perceived benefits of the Internet. Suggestions are put forth to the relevant authorities toward having a digital inclusion policy for persons with disabilities so that they can remain competitive in the employment market.